Размножение серого журавля, Grus grus, на востоке Украины в зависимости от погодных условий - Винтер, С.В.; Горлов, П.И. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
На основании данных 13 сезонных наблюдений за размножением серого журавля, Grus grus (Linnaeus, 1758), на востоке Украины установлено, что откладка яиц в локальной популяции (на юге ареала) происходит тем позднее, чем ниже среднесуточные температуры воздуха предгнездового периода; при изменении последних на 1,0°С, сроки снесения половины яиц сдвигаются на 1,12 сут, что можно объяснить как состоянием кормовой базы, так и степенью готовности стаций (птицы не строят гнездо до тех пор, пока лед не растает). Аналогичная зависимость показана и для соседей серого журавля по биотопу – кряквы (Anas platyrhynchos) и певчего дрозда (Turdus philomelos). Предположено, что связь между сроками начала гнездования и температурами предгнездового периода видоспецифична и характерна для большинства птиц умеренных широт с сезонным климатом. Thirteen breeding seasons of Common Crane, Grus grus (Linnaeus, 1758), in the east of Ukraine are analyzed. Dates of egg laying in a local population in the south of breeding range are found to be so later as daily average air temperatures before breeding season are lower. Median dates of egg laying are altered by 1.12 days as these temperatures change by 1.0˚C. The mechanism, which explains such a phenomenon, is proposed: low temperatures before breeding season influence the terms of Common Crane breeding directly (birds can not build the nest before ice thaw¬ing) and indirectly as well (by means of forage reserves). The similar relationship was found for the neighbour species in the same biotopes – Mallard Duck (Anas platyrhynchos) and Song Thrush (Turdus philomelos). Such relationship between the beginning terms of breeding period and air tem¬peratures before breeding is supposed to be specific for different species and typical for the most birds in middle latitudes with temperate climate.